2013
DOI: 10.1155/2013/690906
|View full text |Cite
|
Sign up to set email alerts
|

Distal Humeral Fixation of an Intramedullary Nail Periprosthetic Fracture

Abstract: Distal humeral periprosthetic fractures below intramedullary nail devices are complex and challenging to treat, in particular due to the osteopenic/porotic nature of bone found in these patients. Fixation is often difficult to satisfactorily achieve around the intramedullary device, whilst minimising soft tissue disruption. Descriptions of such cases in the current literature are very rare. We present the case of a midshaft humeral fracture treated with a locking compression plate that developed a nonunion, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Periprosthetic distant humeral fracture after intramedullary nail for humeral shaft fracture is relatively rare in clinical practice. Only a few cases have been reported in literature [1] , [2] , [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Periprosthetic distant humeral fracture after intramedullary nail for humeral shaft fracture is relatively rare in clinical practice. Only a few cases have been reported in literature [1] , [2] , [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The method of choice after periimplant fractures treated with intramedullary nailing appears to be to exchange of the initially implanted nail to a longer device, which was performed in the majority of the published cases [[4], [5], [6]]. However, in some cases with articular fractures plating had been necessary [2]. To our opinion, intramedullary nailing accomplishes the goals of s stabilizing a periimplant fracture after intramedullary knee arthrodesis, maintaining length and rotation as well as saving the bone regenerate according to the nailing after lengthening principles in this specific case.…”
Section: Discussionmentioning
confidence: 99%
“…Periimplant fractures after knee arthrodesis nails are very rare [1] and challenging to treat [2]. Especially high energy trauma is the main risks for these injuries in young patients [3] resulting in complex surgeries [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthrodesis nail breakage or periprosthetic fractures [16] are most uncommon [17,18]. However, these complications need meticulous treatment either by implantation of a longer nail [7] or even plating [19], depending on the location of fracture and the treated bone. Hinarejos et al [18] reported periprosthetic fractures above and below a modular knee arthrodesis nail.…”
Section: Discussionmentioning
confidence: 99%